Developing a Planning and Management System for Protected Areas on Small Islands (The Azores Archipelago, Portugal): the SMARTPARKS Project - Calado,Helena (2014)
Small Islands face particular challenges in their sustainable development, and therefore require specific tailored approaches for planning and management. Unsurprisingly, protected areas have a special role in the conservation of biodiversity and natural resources crucial to the sustainability of such territories. How should the management and planning system of protected areas in small islands be, therefore, structured and operated so it can face the threats and challenges falling upon the already fragile and vulnerable insular ecosystems? This is the central question of SMARTPARKS Project. The core objective of the project consists of the conceptual development of a planning and management system for protected areas that can be integrated with the territorial management instruments in force, and that takes into consideration the specificities of insular ecosystems, correcting or perfecting the insufficiencies or flaws already pointed out to traditional planning systems of protected areas. This paper presents the SMARTPARKS Project, its rationale and main outcomes. Taking Pico Island Natural Park (Azores, Portugal) as its case study, the SMARTPARKS Project has adopted the ecosystem approach and the conciliation of conservation objectives with human needs and activities. Throughout its five tasks several studies were developed, and contributed to the functional analysis (developed during the last task) of each protected area constituting the Island Natural Park, in terms of their conservation and development values. This innovative application allows not only an integrated assessment of the protected areas but also a sustained monitoring.